Utilising micron-scale 3D printing to investigate particulate interactions for respiratory applications - Marsh, Georgina E. (2018)
In order to achieve drug delivery via the respiratory route, an understanding of particulate interactions is of vital importance. For successful delivery to the distal airways, an aerodynamic diameter of less than 5 µm must be achieved. However, particles of this size presents a difficult formulation challenge, due to the inherent cohesiveness between particles and adhesion to the device, due to the high surface to volume ratio of such small particles, causing the particles to clump together. This tendency will thereby cause a reduction in dispersion, aerosolisation and device efficiency; for this reason dry powder inhalers (DPIs) invariably fail to achieve a fine particle fraction efficiency above 15%.